Gestational Age Specific Anthropometric Percentile Charts Of Newborns At Kathmandu Medical College Teaching Hospital - Manandhar, Sunil Raja; Manandhar, Dharma Sharna (Journal of Kathmandu Medical College, 2015)
Background: A gestational age specific c birth weight, length and head circumference centile chart will help to identify intrauterine growth of a baby. Since the first published gestational age specific anthropometric study done in Nepal by Manandhar DS et al in 1993-94, there have been significant changes in socioeconomic conditions with improved health indicators. This study was done for identifying any changes in anthropometric measurements of the newborns born at Kathmandu Medical College Teaching Hospital (KMCTH). Objectives: To produce gestational age specific c birth weight, length and head circumference centile charts of the New born babies born at KMCTH and to calculate incidence of low birth weight (LBW) babies at KMCTH. Methods: This is a cross sectional observational study. Study was done at labour room, operation theatre, special care baby unit and postnatal wards of KMCTH. Study period was from 18th Aug 2011 to 28th Nov 2012 (15 months duration). Within 24 hours of birth, baby’s weight, length and head circumference were measured by medical officers and post graduate Residents of the Paediatrics Department. Mother’s weight, height and ethnicity were also recorded. Maturity of the baby was assessed by maternal history and corroborated by using modified Ballard score and Obstetric USG (Ultra sonogram) findings. Data were entered in excel database programme and later transferred into SPSS (Statistical package of social science) 16. Mean, standard deviation, range and percentiles values at different gestational age specific c groups were calculated. Results: A total of 2029 live babies without gross congenital malformations were included in this study, among which 57% (1154) were male. While analyzing maturity assessment, 89.1% (1808) were term, 8.7% (176) were preterm and 2.2 % (45) babies were post term. Mean birth weight at 40 weeks of gestation was 3.10 kg with Standard Deviation (SD) of 0.4 kg, mean head circumference was 34.0 cm (SD 1.2 cm) and mean length was 49.2 cm (SD 2.2 cm). Out of 2029 babies, 16.2% (328) babies were low birth weight (LBW) and 1.4% (28) babies weighed >4 kg. Conclusion: Percentile charts of newborns will help to assess the intrauterine growth of babies. Further more studies of these percentile charts will help to produce national level percentile charts of newborns of Nepal. DOI: http://dx.doi.org/10.3126/jkmc.v3i3.12244 Journal of Kathmandu Medical College Vol. 3, No. 3, Issue 9, Jul.-Sep., 2014,Page: 97-101